The watch moral: marc-antoine Jullien and the art of ruling up and educate yourself - Maria Helena Camara Bastos (FahrenHouse, 2011)
They routinely look at the hours when many devices that control the weather. Of the most simple to complex, man has sought ways to manage time and to control this time. Internalized and na- turalized such procedures as part of individual and collective culture, habits and mores of contemporary so- ciety. Modernity is a privileged historical period to study the mechanisms of power-knowledge of the processes of subjection of modern man, with various procedures and techniques of government itself. From the perspective of education and standardization of time is the present study, which analyzed the contribution of Marc-Antoine Jullien (1775-1848), especially his works for the employment of time, which set out prin- ciples of writing practices of self, subjectivity the subject and the construction of individual and social me- mory. Aims to discuss the organization of time, its pedagogical power, which the author argues for the moral formation of man and social, allowing you to develop the capacity to govern and educate yourselves. Metho- dologically, lies in the perspective of writing practices and representations of the time. The weather, yesterday and today, remains a flagship concept and practice for man.